Destination Image as Mediation: Factors Affecting Customer Satisfaction in the Natuna Food Industry - Samara, Emil; Ulum, Ihyaul; Juliati, Ratih (University of Muhammadiyah Malang, 2023)
Customer satisfaction is an essential factor related to a person's assessment of a product and the main topic of the food industry. This study analyzes the influence of product quality, price, and tourist destination variables on customer satisfaction through destination image as mediation. The sampling technique for this research is a non-probability sampling technique by accidental sampling. The characteristics of the sample respondents in this study were those who had visited and consumed Natuna culinary specialties twice at the Tanjung Beach Tourism Object in Northeast Bunguran District. Data collection was carried out by distributing questionnaires directly to the research object. The sample in the study amounted to 200 respondents. The data analysis method uses Structural Equation Modeling with the AMOS program. The results show that product quality, price, tourist destinations, and destination image affect customer satisfaction. Destination image can mediate tourist destinations on customer satisfaction. Meanwhile, destination image does not judge the impact of price and product quality on customer satisfaction.